Analysis of Efficiency and Effectiveness Levels in Financial Management in Serba Jadi Village, Sunggal (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The research approach used in this study is qualitative descriptive, aiming to provide a clear and systematic description of the existing conditions related to village financial management. This research was conducted in Serba Jadi Village, Sunggal Subdistrict, Deli Serdang Regency, as a case study to understand the implementation of financial management at the village level. The type of data used in this study is secondary data obtained from official village documents, reports, and other relevant administrative records. Data collection techniques include observation and documentation, which were carried out to ensure the accuracy and completeness of the information analyzed. The data analysis technique employed is descriptive research, which functions as a systematic method of thinking or review to describe, interpret, and present conditions that occurred during the research period. The analysis focuses on assessing financial performance using efficiency and effectiveness indicators. The results of the study indicate that the Efficiency Ratio shows the financial management of Serba Jadi Village falls into the category of inefficient, reflecting the imbalance between costs incurred and outputs achieved. Meanwhile, the Effectiveness Ratio demonstrates that the financial management of Serba Jadi Village is categorized as effective, indicating that revenue targets and planned objectives were generally achieved despite efficiency limitations.